2012
DOI: 10.1016/j.jcma.2012.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Cranial ultrasonographic findings in healthy full-term neonates: A retrospective review

Abstract: The incidence of minor and major anomalies detected by cranial ultrasonographic screening examinations in healthy full-term neonates is 6.3% and 0.06%, respectively. Thus, cranial ultrasonographic screening testing may play a role in the early diagnosis of intracranial anomalies of otherwise healthy neonates. However, this examination cannot exclude or detect all cranial abnormalities, including many potential neurologic diseases of neonates, so continuing clinical diligence is still important for all infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 35 publications
2
9
1
5
Order By: Relevance
“…In this study, we reported a low rate of significant abnormal findings in full-term newborns (0.19%). As confirmed by others, 16,18 MRI has the highest sensitivity for detecting brain abnormalities in neonates. In the present study, all neonates found with HUS abnormalities underwent MRI to confirm the lesions.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…In this study, we reported a low rate of significant abnormal findings in full-term newborns (0.19%). As confirmed by others, 16,18 MRI has the highest sensitivity for detecting brain abnormalities in neonates. In the present study, all neonates found with HUS abnormalities underwent MRI to confirm the lesions.…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, the presence or absence of neonatal jaundice, multiple pregnancy, neurological symptoms, maternal drug use, congenital infections, autoimmune diseases, antidepressant maternal therapy, and gestational or diabetes mellitus. Ultrasound findings were categorized into three groups 18 : normal or nonsignificant (including normal and normal variations: mild ventricular asymmetry, mild periventricular echogenicity, mild frontal or occipital horn prominence, septum pellucidum cysts, choroid plexus irregularity, mild choroid plexus echogenicity), minor anomalies (thalamic-striatal vessels' echogenicity, enlarged cysterna magna, choroid plexus or subependymal cysts, mild ventricular enlargement, intraplexus hemorrhage, ventricular irregularity, periventricular echogenicity, and subependymal echogenicity), and major anomalies as described in Table (anomalies of the corpus callosum, ventriculomegaly and hydrocephalus, ultrasonographic signs of hypoxic-ischemic injury calcifications, hemorrhages, abnormal echogenicity of parenchyma, and frontal horn prominence associated with an adjacent suspected porencephalic cyst).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall and in all subgroups of weight and gestation for any IVH and high grade IVH, our rates of IVH are higher than those reported in HICs. The difference is smallest in the <1500g and <28 week gestation groups and largest in babies weighing >1500g or >37 weeks, suggesting in our setting it could be the higher weight and later gestation babies that could bene t most from modi cation of risk factors (13)(14)(15)(16)26) .…”
Section: Discussionmentioning
confidence: 71%
“…Prenatal use of betamethasone has shown to provide some protection against IVH. Postnatal use of indomethacin for prevention of IVH is under trial [4,5].…”
Section: Discussionmentioning
confidence: 99%